A Collaborative Model of Humanitarian Assistance for Maximum Coverage of Areas Affected by Natural Disasters - Golnush Jahromi Rajabi; Razieh KeshavarzFard (دانش پیشگیری و مدیریت بحران)
Background and objective Natural and human-made disasters have long-term, negative, and sometimes irreparable impacts and consequences. Proper response to these disasters requires effective management of relief services. Influential parties in such operations include humanitarian organizations, donors, and the government. One of the solutions to increase performance in emergency and humanitarian supply chains is to utilize the capacities of non-governmental organizations (NGOs). This study aims to present a collaborative model based on game theory that examines the cooperation between donors, humanitarian organizations, the government, and NGOs. Method The collaborative model is designed based on the problem of maximum coverage of damaged areas caused by a natural disaster. By considering the number and diversity of players, it takes into account the extent of the disaster and the number of affected areas in relief assistance. It also considers the quality of relief services and the competence of NGOs. This can allow for a default order to prioritize qualified NGOs with the required capacities in the event of a disaster. The developed model was solved using a hypothetical numerical example and GAMS software, and underwent a sensitivity analysis. Results The results obtained from the model provide valuable insights into the optimal actions of each player in the humanitarian supply chain during a disaster. This model takes into account the capacities and capabilities of each player, as well as the quality of services provided by the private sector, allowing for more efficient allocation of resources and ensuring maximum coverage of affected areas. The model also considers qualitative assessments conducted in the pre-disaster period and allows for prioritization of qualified NGOs during a disaster. This can significantly improve the effectiveness of disaster management efforts. Conclusion The collaborative model is designed based on the problem of maximum coverage of damaged areas caused by a natural disaster. By considering the number and diversity of players, it takes into account the extent of the disaster and the number of affected areas in relief assistance. This can significantly improve the effectiveness of disaster management efforts. It also considers the quality of relief services and the competence of NGOs.